2021
DOI: 10.1136/bmjopen-2021-051094
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to educational adaptations and social life at school experienced by young people with CFS/ME: a qualitative study

Abstract: ObjectivesTo explore factors perceived as positive or negative among young people with chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) in relation to school and everyday life.DesignA qualitative study with semistructured individual interviews performed at the local hospital or at the informants’ homes between September 2017 and January 2018, with an additional telephone interview to collect data on experiences from the COVID-19 pandemic, conducted in September 2020. Data were analysed using a groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…40 Indeed, several studies have recommended better training and educational initiatives for physicians 10,41 and for school personnel. 25 Our participants gave many examples of encounters with healthcare workers where they thought that the professionals had little knowledge of ME/CFS, and that their attempts to inform and educate them, in many cases, was futile. Such lack of knowledge could also create challenges to delivering personalised services to the individual ME/CFS sufferer; delivering personalised care being seen as a top priority for the Norwegian healthcare service.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…40 Indeed, several studies have recommended better training and educational initiatives for physicians 10,41 and for school personnel. 25 Our participants gave many examples of encounters with healthcare workers where they thought that the professionals had little knowledge of ME/CFS, and that their attempts to inform and educate them, in many cases, was futile. Such lack of knowledge could also create challenges to delivering personalised services to the individual ME/CFS sufferer; delivering personalised care being seen as a top priority for the Norwegian healthcare service.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that primary care physicians used social and cultural knowledge (insight gained from the media and the Internet and through observations of patients outside the clinical setting) instead of biomedical knowledge in diagnosing ME/CFS 40 . Indeed, several studies have recommended better training and educational initiatives for physicians 10,41 and for school personnel 25 . Our participants gave many examples of encounters with healthcare workers where they thought that the professionals had little knowledge of ME/CFS, and that their attempts to inform and educate them, in many cases, was futile.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations